2012
DOI: 10.1103/physrevx.2.011005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Demagnetization Measurements Using Extreme Ultraviolet Light: Comparison of Electronic and Magnetic Contributions

Abstract: Ultrashort pulses of extreme ultraviolet light from high-harmonic generation are a new tool for probing coupled charge, spin, and phonon dynamics with element specificity, attosecond pump-probe synchronization, and time resolution of a few femtoseconds in a tabletop apparatus. In this paper, we address an important question in magneto-optics that has implications for understanding magnetism on the fastest time scales: Is the signal from the transverse magneto-optical Kerr effect at the M 2;3 edges of a magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
92
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 29 publications
2
92
1
Order By: Relevance
“…However, the fact that changing the relative magnetization direction of the Fe layer relative to the Ni layer (see below) causes an increase or decrease of the observed Fe magnetization, rules out such measurement artifacts. In addition, in a previous publication 17 we showed that the nonmagnetic contribution to the asymmetry parameter is small (0.2%) compared with the amplitude of demagnetization (20%), demonstrating that XUV T-MOKE can sensitively probe element-selective spin dynamics. The layer-selective time traces of the magnetic asymmetries at the 3p absorption edges of Fe and Ni, at fluencies of F≈2 mJ cm − 2 , are plotted in Fig.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…However, the fact that changing the relative magnetization direction of the Fe layer relative to the Ni layer (see below) causes an increase or decrease of the observed Fe magnetization, rules out such measurement artifacts. In addition, in a previous publication 17 we showed that the nonmagnetic contribution to the asymmetry parameter is small (0.2%) compared with the amplitude of demagnetization (20%), demonstrating that XUV T-MOKE can sensitively probe element-selective spin dynamics. The layer-selective time traces of the magnetic asymmetries at the 3p absorption edges of Fe and Ni, at fluencies of F≈2 mJ cm − 2 , are plotted in Fig.…”
Section: Resultsmentioning
confidence: 49%
“…Measuring I r (H) for these two opposite field directions gives an artifact-free and sensitive measurement of the magnetic state 16,17,26 . The resonantly enhanced static magnetic asymmetry at the Fe and Ni 3p absorption edges (52 and 66 eV, respectively) can be clearly assigned to the magnetic state of the Fe and Ni layers, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrying out these two comparative measurements, we find that Ni on MgO demagnetizes with a time constant of 120 ± 14 fs (see SM [28] and compare also with Refs. [2,7]), which is almost three times larger than in the case of Ni on Au with 42 ± 8 fs. This significant difference in the demagnetization times of Ni on different substrates clearly shows that the loss of magnetic moment via spin-flip scattering takes considerably longer than the dominant demagnetization mechanism for Ni on Au.…”
mentioning
confidence: 95%
“…Numerous experiments have been conducted, in addition to theoretical efforts, to elucidate the underlying microscopic mechanisms that can result in a surprisingly fast loss of magnetic order on a femtosecond (fs) time scale [2][3][4][5][6]. The microscopic mechanisms responsible for this photoinduced ultrafast loss of magnetic order can be classified as spin-flip scattering phenomena [2,7,8] and spin transport phenomena [9][10][11][12]. Today we know that both processes clearly contribute to the ultrafast demagnetization and that the contributions of both mechanisms depend on the details of the material system and multilayer structure [8,[12][13][14][15].…”
mentioning
confidence: 99%